Char-diesel slurry fuels for microgeneration: Emission characteristics and engine performance. (15th September 2020) - Hammerton, James M.; Li, Hu; Ross, Andrew B.
Abstract: Diesel engine generators are one of the major methods for off-grid and on-demand electricity generation, particularly in the remote areas of some developing countries. However, access to fossil diesel is often limited by supply or price. In many regions, biomass is an abundant source of energy, but many types are not suitable for producing traditional liquid biofuels such as biodiesel. This paper explores the use of so called 'slurry fuels' produced by the blending of micron sized particles of carbonaceous material in diesel and assesses whether these 'slurry fuels' can be used in a standard diesel engine generator with minimal modification. Two types of micronized carbon chars were added to diesel, produced by either pyrolysis or hydrothermal carbonization of biomass. The results indicated that at high engine power, the micronized carbon slurry fuels can be run at a similar efficiency as pure diesel. The major issues identified included high engine wear and the blockage of the fuel injector. Hydrothermal carbonization was found to be the best thermal conversion route for producing micronized carbon in terms of emissions when blended with diesel. Highlights: Micronized carbon slurries can be used to fuel small high speed engines. Micronized carbon slurries potentially viable for microgeneration. Hydrochar slurry produced fewer emissions than pyrolysis slurry from same material. Contamination of lubrication oil is a serious long-term issue. Particle emissions are much less than the ash content of the fuel would suggest.